High-quality development of China’s power industry: Measurement, spatial pattern, and improvement paths - Sha Yu; Yongjian Pu; Lefeng Shi; Hao Yu; Yixiang Huang (Chinese Journal of Population, Resources and Environment, 2023)
As the largest manufacturing country, China is striving to improve the development quality of its power industry with the goal of Carbon Peaking and Carbon Neutrality, in order to sustain its high-quality economic growth. In this regard, it is of importance to reveal both the regional development level of China’s power sector and its characteristics in terms of inspiring the next improvement direction. Motived by this purpose, this paper constructs an evaluation indicator system from three dimensions at the province level based on the connotation of high-quality development of the power industry (HDPI). Next, it calculates the HDPI indexes of 30 provinces and explore their development trend and spatial pattern. The results indicate that the total comprehensive performance of all regions was improved in general in the recent decade, but the spatial distribution characteristics of clean, low-carbon, safe and efficient are different. In the aspects of improvement space in future, not only do actively ameliorate the related management regimes or technical fields so as to improve the corresponding indicators’ value, but also passively rely on the macro-development such as China’s urbanization level improvement, technological level improvement, and industrial structure upgrading as usual.